Tuberculosis treatment abandonment in Baixada Santista in the period 2006-2016 and its risk factors (Research, Society and Development, 2022)
Objective: To analyze the association between epidemiological variables and treatment outcomes for tuberculosis in cases of the disease reported in the municipalities of Baixada Santista between 2006-2016. Methods: A ecological study that aims to analyze 18,550 cases of Tuberculosis reported in Baixada Santista between 2006-2016 results: The variables with the greatest association with the dropout outcome were drug addiction (OR: 0.27); housing (OR: 0.17) and type of treatment (OR:2.24). Conclusions: The improvement in abandonment and cure rates for tuberculosis cases reported in Baixada Santista are linked to the promotion of public policies and health actions studied, such as the DOTs strategy and improvement in the quality of life of populations in social vulnerability.